Designing Knowledge Economies for Disaster Resilience: Case Studies from the African Diaspora - Pamela Waldron-Moore, Pamela Waldron-Moore (Catastrophes in context, 2024)
Disaster research has been studied from many angles, seldom targeting its implications for vulnerable territories in Africa. Entities most subject to the effects of climate change are often undeveloped and located in disadvantaged regions. Post-disaster communities need to scrutinize the social, political, economic, and cultural structures that stagnate sustainable growth. Acknowledging that low economic development and high climate costs cannot coexist, this collected volume interrogates the challenge for disaster-prone territories to determine strategies for restructuring and redesigning their environment. This book proposes the creation of knowledge economies, whereby empowered communities may produce innovative knowledge translatable across the African diaspora.